Fournier's gangrene in a man on empagliflozin for treatment of Type 2 diabetes. Issue 11 (17th October 2017) - Kumar, S.; Costello, A. J.; Colman, P. G.
Abstract: Background: Sodium‐glucose cotransporter 2 (SLGT2) inhibitors has been associated with an increased risk of genital infections secondary to increased glycosuria. Case Report: We report a case of a 41‐year‐old man with type 2 diabetes treated with empagliflozin and metformin who presented with scrotal swelling. He described multiple preceding episodes of genital thrush for which he self‐administered over‐the‐counter anti‐fungal treatment. On examination, he was afebrile and hemodynamically stable. Perineal examination revealed grossly swollen and indurated scrotum with bilateral inguinal lymphadenopathy. Investigations showed elevated inflammatory markers and HbA1c of 99 mmol/mol (11.2%). Computed tomography revealed features consistent with Fournier's gangrene. He underwent emergency exploration and debridement under anaesthetic with a later return to theatre for further exploration, washout and application of a vacuum dressing. He then received a split skin graft to his perineum. He required a 2‐week course of intravenous antibiotics and was discharged home on oral antibiotics. Empagliflozin was ceased on admission and he was commenced on a basal bolus insulin regimen for glycaemic optimisation. Conclusion: There is a wide clinical spectrum of genital infections associated with SGLT2 inhibitors with most being generally mild and easily treated. However, risk factors such as diabetes, obesity, immunosuppressed states, smoking, alcohol abuse and end‐stage renal or liver failure may increase the risk of potentially more severe infections such as Fournier's gangrene. Timely cessation of SGLT2 inhibitors in individuals with multiple risk factors may help prevent progression to more severe genital infections.